Detail of Pigeon Fountain - Ghosh, Ayan (Jio Institute, 2023)
At the rear of the BMC building, at the end of the garden, Frederick Stevens installed a pyav (fountain) which was a source of drinking water for horses. This fountain has figures of birds on them, hence known as the Pigeon Fountain.